Manajemen Diabetes Melalui Edukasi 5 Pilar di Ruang Rawat Penyakit Dalam: Studi Kasus - Syifa Aulia Hafitriany; Kurniawan Yudianto (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Background: Diabetes mellitus is a chronic metabolic disorder caused by inadequate insulin action. Poor disease control can lead to complications such as neuropathy, commonly marked by tingling or sensory loss. Effective prevention requires structured management through the five pillars of diabetes care. This case study describes the application of these pillars in a patient with hyperglycemia. Case: A 58-year-old male with diabetes mellitus presented with reduced sensation in the feet, abdominal discomfort, and consistently elevated blood glucose levels. The patient had limited disease knowledge and misconceptions related to diabetes self-management. Intervention: Education on the five pillars of diabetes was provided using a structured approach consisting of three self-care pillars and two collaborative pillars. Leaflet-based educational materials developed by the author were used to facilitate understanding for both the patient and family. Results: Following the intervention, the patient demonstrated increased knowledge, awareness, and improved ability to manage hyperglycemia. The family also showed enhanced understanding and support for diabetes care. Conclusion: Nurse-led education using the five pillars of diabetes effectively improves knowledge, awareness, and self-management abilities in individuals with diabetes mellitus, contributing to better glycemic control and prevention of complications.